2004
DOI: 10.1016/j.jtcvs.2003.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Xenoreactivity and engraftment of human mesenchymal stem cells transplanted into infarcted rat myocardium

Abstract: Adult human mesenchymal stem cells did not induce xenoreactivity in vitro in previously unexposed immunocompetent Sprague-Dawley rats. However, although mesenchymal stem cells are transplantable across allogeneic barriers, transplant rejection can occur in a xenogenic model. When transplanted into an immunoincompetent host, adult human mesenchymal stem cells showed persistent engraftment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
167
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(177 citation statements)
references
References 26 publications
(48 reference statements)
8
167
1
1
Order By: Relevance
“…Three years later, a similar group of researchers reported again the successful transplantation of mouse BMSCs into infarcted rat heart [10]. However, 2 other studies, both first-authored by Grinnemo, reported unsuccessful transplantation of human BMSCs into infarcted rat heart [11,12]. The discrepancy could perhaps be explained by differences in immunological properties between human and mouse BMSCs.…”
Section: Stem Cells and Developmentmentioning
confidence: 99%
“…Three years later, a similar group of researchers reported again the successful transplantation of mouse BMSCs into infarcted rat heart [10]. However, 2 other studies, both first-authored by Grinnemo, reported unsuccessful transplantation of human BMSCs into infarcted rat heart [11,12]. The discrepancy could perhaps be explained by differences in immunological properties between human and mouse BMSCs.…”
Section: Stem Cells and Developmentmentioning
confidence: 99%
“…Besides their capacity to differentiate into mesenchymal and nonmesenchymal cell lineages (7,8) and their potential clinical application for the repair of damaged tissues, several recent studies have shown that bone marrow-derived MSCs (BM-MSCs) regulate the immune response, including in vitro inhibition of T cell proliferation, B cell function, and dendritic cell maturation (9)(10)(11)(12)(13). Some researchers have reported the use of BM-MSCs to treat allograft rejection and acute graftversus-host disease as well as to alleviate experimental autoimmune encephalomyelitis, collagen-induced arthritis (CIA), and autoimmune myocarditis (11,(14)(15)(16)(17)(18)(19)(20). However, the specific molecular and cellular mechanisms involved in the immunoregulatory activity of BM-MSCs remain a subject of controversy.…”
mentioning
confidence: 99%
“…Such immunological characteristics of BMSCs theoretically can make them impervious to immunorejection following xenogenic transplantation, irrespective of the use of immune suppression. Previous studies have reported conflicting results following xenogenic BMSCS transplantation into non-immunosuppressed hosts, ranging from no survival to differentiation into destination cells [9,19,28,30]. However, in our literature review, we were unable to find any study that had investigated the results of xenogenic BMSCs transplantation in a spine fusion model.…”
Section: Discussionmentioning
confidence: 83%